(untitled) (The Review of Diabetic Studies, 2025)
Background: High-sensitivity cardiac troponin (hs-cTn) assays have revolutionized the early diagnosis of acute myocardial infarction (AMI) in emergency department (ED) settings. Their ability to detect low troponin concentrations enables rapid clinical decision-making and improved patient outcomes. Objective: This systematic review aimed to evaluate the diagnostic accuracy of hs-cTn assays for early detection of AMI in ED patients and to assess the performance of rapid diagnostic algorithms and emerging approaches. Methods: A systematic search of PubMed, Scopus, Web of Science, Embase, and Google Scholar was conducted up to December 2025. Twelve studies were included, encompassing prospective, retrospective, and multicenter diagnostic accuracy designs. Data on sensitivity, specificity, predictive values, and area under the curve (AUC) were extracted. A narrative synthesis approach was applied due to heterogeneity. Results: High-sensitivity troponin assays demonstrated excellent diagnostic performance, with AUC values ranging from 0.84 to 0.98. Sensitivity and negative predictive value were consistently high (≥96% and ≥99%, respectively), supporting safe rule-out of AMI. Rapid algorithms (0/1-hour and 0/2-hour) effectively classified 50–66% of patients as low risk. Absolute troponin changes outperformed relative changes, while point-of-care testing and machine learning approaches enhanced diagnostic efficiency. However, specificity and positive predictive value were comparatively lower, particularly in early presentations. Conclusion: Hs-cTn assays provide highly accurate and reliable tools for early AMI detection in ED settings. Rapid diagnostic strategies significantly improve clinical workflow, although careful interpretation is required to address reduced specificity.